1999
DOI: 10.1002/(sici)1097-0045(19990601)39:4<291::aid-pros10>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

GM‐CSF as a systemic adjuvant in a phase II prostate cancer vaccine trial

Abstract: BACKGROUND. Recombinant human granulocyte-macrophage colony-stimulating factor (GM-CSF; Leukine [sargramostim], Immunex Corp., Seattle, WA) was administered to a subgroup of 44 patients in a phase II clinical trial for prostate cancer using DC pulsed with HLA-A2-specific prostate-specific membrane antigen (PSMA) peptides. Our purpose was to determine if GM-CSF caused any enhancement of patients' immune responses, including enhancement of clinical response to the DC-peptide treatment. This report compares the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Of greater concern, this trial also observed a trend toward worse overall survival in those patients who received GM‐CSF. These findings mirror results from earlier clinical studies where either reduced immunogenicity or a failure to augment immunogenicity was seen in vaccine regimens using GM‐CSF as an adjuvant compared to a control arm that did not receive the cytokine (70–73). The mechanism behind the reduced immune‐responsiveness observed in the presence of exogenous GM‐CSF remains to be completely determined.…”
Section: A Critical Need For Better Immunologic Adjuvantssupporting
confidence: 83%
“…Of greater concern, this trial also observed a trend toward worse overall survival in those patients who received GM‐CSF. These findings mirror results from earlier clinical studies where either reduced immunogenicity or a failure to augment immunogenicity was seen in vaccine regimens using GM‐CSF as an adjuvant compared to a control arm that did not receive the cytokine (70–73). The mechanism behind the reduced immune‐responsiveness observed in the presence of exogenous GM‐CSF remains to be completely determined.…”
Section: A Critical Need For Better Immunologic Adjuvantssupporting
confidence: 83%
“…Although satisfactory and clinically applicable cryopreservation methods for DCs have been described [18][19][20][21], methods to cryopreserve products transduced with Adv vectors have been little studied [22]. In most clinical trials reported to date, DCs were freshly prepared for each administration either from fresh blood [23][24][25][26][27], leukapheresis products [23,28,29], or from frozen aliquots of PBMCs obtained by leukapheresis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Given all of these immunostimulatory properties, several groups have been investigating GM-CSF as a vaccine adjuvant [18][19][20]. Other groups have investigated administration of GM-CSF alone as a means of eliciting anti-tumor immunity.…”
Section: Granulocyte-macrophage Colony Stimulating Factor (Gm-csf)mentioning
confidence: 99%